PENGARUH KADAR PROTEIN YANG BERBEDA TERHADAP PERTUMBUHAN IKAN GURAMI (Osphronemus gouramy) - Nasir Ahmad; Suharun Martudi; Dawami Dawami (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
The purpose of this study is to determine the effect of different protein levels on the growth of gourami (Osphronemus gouramy). The study was conducted for 60 days starting from June to August 2017, at Kelurahan Pasar Melintang, Teluk Segara Subdistrict, Bengkulu City. The research design used was Completely Randomized Design (RAL) which consisted of 3 treatments with each treatment in repeated 4 times, so that 12 research units were obtained. For container boxs with size 40 cm x 30 cm and water height 25 cm. The number of test fish used for the study amounted to 60 fishes with length of fish 6-8 cm. Fingerprint analysis showed that feeding with different protein content significantly affected weight growth whereas for lengthy growth of fish, feed conversion, feed efficiency and survival have no significant effect. Results from further tests of BNT showed the best treatment. The highest absolute weight on P3 treatment with feed with 40% protein content.